Significance of histologic grading using visual analogue scale in chronic gastritis - Dr. Priyadarshini Monnappa; Dr Gitanjali M. M.; Manjunatha Y. A. (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: Helicobacter Pylori and its association with carcinogenesis has significantly changed the field, establishing new guidelines for the detection of it. Carcinogenicity of H. Pylori necessitates grading the variables with visual analogue scale in accordance to Sydney system classification. The objectives of this study is to assess chronic gastritis and grade with visual analogue scale of Sydney classification.Methods: This is a prospective study of 3 years in which 50 gastric endoscopic mucosal biopsies were included in the study. Grading of the variables were done with reference to Sydney classification. Morphological changes in all cases were studied with special reference to atrophy, dysplasia, metaplasia, neutrophilic infiltration, lymphoid follicle formation, plasma cell infiltration & malignant changes along with identification of H. pylori.Results: Of the 50 cases studied for gastritis, 20 cases (44.4%) had Chronic H. pyloric gastritis followed by 18 cases (38.6%) of chronic gastritis with nonspecific features. Evaluation for graded variables showed 41 cases of gastritis with chronic inflammation of which 22 cases showed H. Pylori positivity. Of the 20 cases of gastritis showed inflammatory activity, 11 showed H. Pylori positivity. H. pylori was seen in 21 cases which could be graded. Of the 15 cases of gastritis showing surface epithelial damage, 9 cases showed H. pylori positivity. Chronic inflammation was most commonly observed and 22 of the 41 cases with chronic inflammation showed H.pylori positivity. Presence of H.pylori was an useful indicator in grading of gastritis.Conclusion: Visual analogue scale is an useful indicator to histologically grade chronic gastritis and detection of H. Pylori and helps in better evaluation of patient in preventing the further progression of the disease.